Variation of genetic diversity over time in local Italian chicken breeds undergoing conservation - Abbadi, Miriam; Zanetti, Enrico; Cassandro, Martino (Acta Agraria Kaposváriensis, 2010)
Aim of this study was to measure the variation of different genetic diversity measures in five Italian local chicken breeds over a four years period of conservation. A total of 413 individuals were chosen for the analysis among the animals born in 2002 (a) and in2006 (b) and genotyped for 20 microsatellite markers. In the animals sampled after four years of conservation activities the loss of alleles occurred, but only for those which had lower frequencies, with a mean number of alleles equal to 7.75 ± 3.08 in the year 2002 and 4.64 ± 1.60 in the year 2006. During the four years of conservation from 2002 to 2006, all breeds showed a not significant decrease of observed heterozygosis, ranging from 2.8% for Robusta Maculata to a maximum of 8.4% for Padovana. Expected heterozygosis showed the same trend, decreasing of 1% for Robusta Lionata to a maximum of 15% for Robusta Maculata. A decrease in the inbreeding coefficient occurred from 2002 to 2006 for Pépoi, Ermellinata di Rovigo and Robusta Maculata breeds, probably due to the unleashing of within breed genetic structures attributable to the rotation of males among the conservation flocks. On the other hand, an increment of the same index was noticed for the Robusta Lionata and Padovana breeds, for which an increase of inbreeding is probably due to the annual selection of individuals for morphological and productive traits. Genetic structure analysis revealed that the best number of populations fitting the dataset was five. Individuals were so assigned to one of five groups, approximately corresponding to the breed of origin. This result shows how no evident genetic structures were detectable within breed, both for 2002 and 2006 individuals. However, an increase in the proportion of membership for each breed has occurred in the year 2006 compared to the data obtained in the year 2002. Results obtained are very useful for planning new strategies for the conservation scheme, including the choice of the animals, a more efficient organization of matings and for the creation of a new selection index based on the maintenance of the existing genetic variation.